Do multiple personal roles promote working energetically in female nurses? A cross-sectional study of relevant factors promoting work engagement in female nurses - Nagisa Okada; Kosuke Yabase; Toshio Kobayashi; Hitoshi Okamura (Komiyama Printing Co. Ltd, 2019)
Abstract Background Like most women, female nurses in the workforce experience life events such as marriage, childbirth, and child-rearing, and carry out numerous personal roles. This may result in an increase in various demands for nurses, and coping with these roles may promote work engagement. However, few studies have focused on work engagement or spillover effects, including those in the family domain, in female nurses with multiple roles. In the present study, we aimed to examine work engagement in female nurses and investigate its relationship with factors such as the presence or absence of multiple personal roles. Methods The subjects of this study were 1225 female nurses working at three general hospitals, each with at least 200 hospital beds in Fukuoka Prefecture, Japan. The cross-sectional design of the study used anonymous self-administered questionnaires. Responses were received from 650 nurses (response rate 53.1%), of which 612 were valid (valid response rate 50.0%). Multiple regression analysis was performed on the 612 responses regarding associations between work engagement and the presence or absence of multiple roles (role as a wife or mother), spillover effects, coping characteristics, job demands, and job resources. Results In general, the work engagement of female nurses was low, as is the case with other female workers in Japan, but work engagement was higher among female nurses with multiple roles than among those without. The regression analysis showed that factors associated with better work engagement in female nurses were family-to-work positive spillover, job resources, coping strategies including "changing a point of view," "active solution for problems," "avoidance and suppression," and the presence of multiple roles. Conclusions The results indicate that in addition to resources in the work domain, a family-to-work positive spillover effect, which is a variable in the non-work domain, may also promote energetic work among female nurses. Therefore, it is necessary for nurses to receive support at work and use effective coping strategies.